Transcriptome alterations in spermatogonial stem cells exposed to bisphenol A - Jin Seop Ahn; Jong-Hyun Won; Do-Young Kim; Sang-Eun Jung; Bang-Jin Kim; Jun-Mo Kim; Buom-Yong Ryu (Animal Cells and Systems, 2022)
Owing to their self-renewal and differentiation abilities, spermatogonial stem cells (SSCs) are essential for maintaining male fertility and species preservation through spermatogenesis. With an increase in exposure to plasticizers, the risk of endocrine-disrupting chemicals exerting mimetic effects on estrogen receptors, such as bisphenol A (BPA), has also increased. This has led to concerns regarding the preservation of male fertility. BPA impairs spermatogenesis and the maintenance of SSCs; however, the transcriptome differences caused by BPA in SSCs are poorly understood. Thus, this study aimed to investigate the transcriptome differences in SSCs exposed to BPA, using RNA sequencing (RNA-Seq) analysis. We found that cell proliferation and survival were suppressed by SSC exposure to BPA. Therefore, we investigated transcriptome differences through RNA-Seq, functional annotation, and gene set enrichment analysis. Our results showed repetitive and abundant terms related to two genes of lysosomal acidification and five genes of glycosaminoglycan degradation. Furthermore, we validated the transcriptome analyses by detecting mRNA and protein expression levels. The findings confirmed the discovery of differentially expressed genes (DEGs) and the mechanism of SSCs following exposure to BPA. Taken together, we expect that the identified DEGs and lysosomal mechanisms could provide new insights into the preservation of male fertility and related research.